Biomarkers of myocardial fibrosis and renal dysfunction in hypertensive patients with type 2 diabetes mellitus - Bilovol, Oleksandr M; Kniazkova, Iryna I.; Kirienko, Oleksandr M.; Bogun, Maryna V; Kirienko, Denis M.; Abramova, Lilya P.; Berezin, A. E.; Березін, Олександр Євгенійович (India: Jadoun Science Publishing Group, 2020)
The aim of the study was to investigate the interaction of circulating levels of sST2, neutrophilic gelatinase-associated lipocalin, and cystatin C with cardiac remodeling in hypertensive patients depending on the presence of T2DM. Methods: The study included 76 mild-to-moderate hypertensive patients, of whom 48 patients were with stage II grade 2 of hypertension and T2DM, and 28 patients with stage II of hypertension without T2DM. The control group consisted of 20 healthy volunteers (mean age of 54.5 ± 3.1 years). All examined persons underwent general clinical examination, determination of indicators of carbohydrate metabolism and lipid profile; insulin resistance was assessed using the HOMA-IR index. Serum levels of soluble suppressor tumorigenicity-2 (sST2), cystatin C, and NGAL were measured using kits for enzyme-linked immunosorbent assay. The structural and functional parameters of the heart and the diastolic function of the left ventricle were analyzed using echocardiography with Doppler sonography. Results: It was found that concentric and eccentric LV hypertrophy, and diastolic dysfunction, occurred more often in hypertensive patients with T2DM than in the hypertensive patients without T2DM. In T2DM patients eccentric and concentric LV remodeling was associated with the levels of sST2 (r = 0.53; P=0.001 and r = 0.55; P=0.001, respectively), cystatin C (r = 0.40; P=0.001 and r = 0.44; P=0.001, respectively) and NGAL (r = 0.38; P=0.001 and r = 0.44; P=0.001, respectively). Backward stepwise regression analyses showed that the most influential determinants of depending variable (LV remodeling) in T2DM patients were sST2 (B-coefficient = 1.9, SD = 0.03; p=0.001) and cystatin C (B-coefficient = 0.92, SD = 0.03; p=0.022), whereas NGAL exhibited weak discriminative ability (B-coefficient = 0.21, SD = 0.01; p=0.16). Conclusion: Cardiac remodeling in hypertensive patients having T2DM was significantly associated with higher levels of sST2 and cystatin C. sST2 had the best potency to predict LV remodeling when compared with NGAL and other biomarkers.
Keywords: hypertension; type 2 diabetes mellitus; soluble suppressor tumorigenicity-2; neutrophilic gelatinase-associated lipocalin; diastolic function